Antihypertensive Treatment in the Postpartum Care of Preeclampsia: A Hemodynamic-Based Approach - Ogamba-Alphonso, Ifeoma; Miller, Erin; Brown-Thomas, Tudi-Max; Katehis, Ioanna; Gitlin, Saige; Maldonado, Delphina; Fernandez De Salvo, Gabriella; Asfour, Tony; Ginsberg, Izzy; Gunabalan, Silpaa; Rajan, Anand; Shah, Keya; Kapoor, Mehak; Gubernikoff, George; Kinzler, Wendy; Chavez, Martin; Heo, Hye; Rekawek, Patricia (American Journal of Perinatology, 2025)
Labetalol and nifedipine are first-line antihypertensives for hypertensive disorders of pregnancy. However, there is limited research comparing their effectiveness based on hemodynamic profiles seen in preeclampsia, such as high cardiac output (CO) and high systemic vascular resistance (SVR). This study assesses whether concordance of antihypertensive treatment with the hemodynamic status on echocardiogram reduces time to achieve target postpartum blood pressure (BP) before discharge.This retrospective cohort study included patients with preeclampsia with severe features who received a postpartum echocardiography, excluding patients with cardiac etiology. Antihypertensive choices were provider-dependent. The CO and SVR were calculated retrospectively from the echocardiogram in collaboration with cardiology. Concordance was defined as patients with high CO (>6 L/min) started on labetalol and high SVR (>1,200 dynes·sec·cm5) started on nifedipine; opposite pairings were discordant. The primary outcome was time to achieve target BP, defined as the period from the start of antihypertensive therapy to when no titration was needed to sustain BPs of less than 140/90 mm Hg. Chi-square and Fisher's tests were used for categorical variables, and Mann–Whitney U test for continuous variables.Of 298 patients, 155 (52%) received concordant therapy and 143 (48%) discordant. Of the cohort, 229 (76.8%) had high SVR and 69 (23.2%) had high CO. Median time to target BP was not significantly different (concordant: 32 hours [interquartile range, IQR: 0–61], discordant: 41 hours [IQR: 4–75], p = 0.13). The concordant group needed fewer titrations to achieve target BP (1 [IQR: 0–2] vs. 2 [IQR: 1–3]; p = 0.008) and were less likely to be discharged home on multiple antihypertensive medications compared with the discordant group (28.9 vs. 42.7%, p = 0.014). Maternal demographics were similar between groups.While time to target BP did not differ, concordance of antihypertensive therapy to postpartum hemodynamics in patients with severe preeclampsia reduced medication adjustments and increased the likelihood of discharge on a single-agent regimen.
Keywords: hemodynamic profiles; preeclampsia; concordant therapy; hypertension; echocardiography